Pembaruan informasi taksonomi nyamuk dan kunci identifikasi fotografis genus nyamuk (Diptera: Culicidae) di Indonesia - Sidiq Setyo Nugroho; Mujiyono Mujiyono (Perhimpunan Entomologi Indonesia, 2021)
The adult female mosquito identification is an important aspect in vector-borne disease surveillances and vector control strategies. Indonesia with high mosquito species diversity faces the problem related to the presence of several important vector-borne diseases, including malaria, chikungunya, dengue fever, filariasis, and Japanese encephalitis. Updated key to the mosquitoes is needed to provide up to date information of the appropriate disease vectors in Indonesia. Currently, before the publication of the checklist of Indonesian mosquitoes by O’Connor & Sopa (1981), there has been no recent information on the number of mosquito genera and subgenera in Indonesia. This article aims to deliver updates on mosquito taxonomic information and provide the identification key of the mosquito genera in Indonesia. So far, a total of 21 genera and 63 mosquito subgenera has been reported in this country. Overall there are three genera and 15 subgenera added from the 1981’s mosquito checklist, Verrallina, Lutzia, and Kimia are added in the list of new mosquito genera.